Bizarre parosteal osteochondromatous proliferation of humerus with unusual presentation: a report of one atypical case - Pradhan, Dilleswari; Swain, Basanta Manjari; Lenka, Anasuya; Samal, Barada Prasanna (International Surgery Journal, 2016)
Bizarre Parosteal Osteochondromatous Proliferation (BPOP) as defined by Nora and colleagues in 1983 (called Nora lesion) is a rare benign, bony lesion and found mostly in metacarpals and metatarsals. BPOP in long bones are very rare. It is an exophytic outgrowth from the cortical surface comprising of bone, cartilage and fibrous tissue. The key radiological features to describe such lesions as calcified and osseous masses. We describe a case of BPOP in a 26 year old female involving the shaft of humerus. The radiological picture is a trabeculated osteolytic lesion. FNA revealed chondroma and histologic picture showed disordered pattern of cartilage, bone and fibrous tissue. This case is reported as the lesion is at a rare site (shaft of Humerus) unusual X-ray picture for the lesion and diagnostic histopathologic picture.